Professional Rugby Union players have a 60% greater risk of time loss injury after concussion: a 2-season prospective study of clinical outcomes. Issue 15 (1st December 2015) - Cross, Matthew; Kemp, Simon; Smith, Andrew; Trewartha, Grant; Stokes, Keith
Abstract : Aim: To investigate incidence of concussion, clinical outcomes and subsequent injury risk following concussion. Methods: In a two-season (2012/2013, 2013/2014) prospective cohort study, incidence of diagnosed match concussions (injuries/1000 h), median time interval to subsequent injury of any type (survival time) and time spent at each stage of the graduated return to play pathway were determined in 810 professional Rugby Union players (1176 player seasons). Results: Match concussion incidence was 8.9/1000 h with over 50% occurring in the tackle. Subsequent incidence of any injury for players who returned to play in the same season following a diagnosed concussion (122/1000 h, 95% CI 106 to 141) was 60% higher (IRR 1.6, 95% CI 1.4 to 1.8) than for those who did not sustain a concussion (76/1000 h, 95% CI 72 to 80). Median time to next injury following return to play was shorter following concussion (53 days, 95% CI 41 to 64) than following non-concussive injuries (114 days, 95% CI 85 to 143). 38% of players reported recurrence of symptoms or failed to match their baseline neurocognitive test during the graduated return to play protocol. Summary and conclusions: Players who returned to play in the same season after a diagnosed concussion had a 60% greater risk of time-loss injury than players without concussion. A substantial proportion of players reported recurrence of symptoms or failed to match baseline neurocognitive test scores during graduated return to play. These data pave the way for trials of more conservative and comprehensive graduated return to play protocols, with a greater focus on active rehabilitation.